Jump higher, run faster: effects of diversified sport participation on talent identification and selection in youth basketball - Arede, J.; Esteves, P.; Ferreira, A. P.; Sampaio, J.; Leite, N. (Journal of Sports Sciences, 2019)
The aims of this study were to examine the medium-term effects of previous experiences during early stages of sport development on physical capacities of under-13 (U-13) talented basketball players and, to identify variables that discriminated under-14 (U-14) national team training camp selection. Anthropometrical and physical measurements were collected during a basketball training camp. Previous sport experiences (6-10 years), maturity offset, power outputs for jumping and sprinting were determined. A cluster analysis was used to allocate the subjects according to their different levels of sport experiences (more specialized vs. less specialized) to allow creating a dummy variable for the subsequent analysis of the physical variables. A stepwise discriminant analysis was computed to identify the construct that best classifies selected and non-selected players for U-14 national team training camp. The less specialized group outscored more specialized in all physical parameters, irrespectively of gender. The Abalakov Jump Peak Power and Predicted Adult Height (PAH) could successfully discriminate selected from non-selected players for U-14 national team training camp in boys and PAHin girls. The diversified and non-specific sport stimulus during early ages seem to be determinant to the acquisition and development of fundamental movement skills of talented basketball players.